An update on the cecectomy technique in roosters anesthetized with isoflurane used in subsequent amino acid digestibility experiments. (6th March 2019) - Mansano, C F M; Macente, B I; Silva, P do E S; da Rocha, R W; Escobar, A; Sakomura, N K; Khan, K U; Fernandes, J B K; da Silva, E P
ABSTRACT: This work aims to study an alternative technique of cecectomy in roosters using inhalation anesthesia for subsequent use in digestibility experiments. A total of 30 adult chickens of Leghorn breed were used with an average age of 27 wk. The birds were preoxygenated, and the anesthetic induction was performed using isoflurane diluted in oxygen. After proper muscle relaxation, endotracheal intubation was performed using a Murphy catheter and kept in anesthesia under mechanical ventilation with a constant monitoring of electrocardiography variables, heart rate, oxyhemoglobin saturation, and body temperature during the surgical procedure. An incision of approximately 3 cm was made between keel and cloaca in order to expose and extirpate the cecum followed by a simple ligature. The opening of the peritoneal cavity was closed in 2 ways: Sultan suture technique was used for closing the abdominal wall and modified Cushing intradermic continuous points for closing the skin. The time for anesthesia induction and preoperational period noted to be 10 ± 2 min. Surgical procedures completed in 7 ± 1.5 min. No intraoperatively and postoperatively harm observed in animals. Water was immediately provided after the birds returned to cages and feed offered after 24 h of surgery. In remaining birds, no abnormalities were observed during and after the experimental period (3 mo). The present study describes a promising update on cecectomy technique regarding anesthesia induction and surgical procedures in roosters using potential drugs and safer surgical materials without any trans- and postoperative complications.